The architect's studio companion : rules of thumb for preliminary design - Iano, Joseph; Allen, Edward, 1938- (Hoboken, New Jersey : Wiley, 2022)
'The Architect's Studio Companion is a robust, user-friendly resource that keeps important information at your fingertips throughout the design process. It includes guidelines for the design of structure, environmental systems, parking, accessibility, and more. This new seventh edition has been fully updated with the latest model building codes for the U.S. and Canada. New material in this edition includes comparisons to show the embodied carbon impacts of structural system choices which is highly relevant to new design practices. The guiding principle for The Architect's Studio Companion is the presentation of simplified design guidelines for building technical systems, particularly in certain systems that have a significant influence on the form and organization of the building. Using this book, designers can incorporate the impacts of these systems while working in the fluid manner inherent to the earliest stages of building design. More than just a reference, this book is a true companion that no practicing architect or student should be without'--
Includes bibliographical references and index.
Keywords: Architectural design -- Handbooks, manuals, etc